Бытовые печи, камины и водонагреватели - Соснин Юрий Павлович (Стройиздат, 1985)
Экземпляры: ф. 2 (20140211) / Инвентарный номер: 100652 / Цена: 10.00 / Сис.шифр: 38.625 / Авт.знак: С 66 / ГРНТИ: 67 / ББК: 38.62